EFFECTS OF VARYING LEVELS OF CALCIUM IN RATIONS FOR BUFFALO (BUBALUS BUBALIS) CALVES ON GROWTH RATE AND NUTRIENT DIGESTIBILITY - M. I. Anjum; I. H. Mirza; I. Begum; S. Javaid (Journal of Animal and Plant Sciences, 2014)
Twelve Nili-Ravi buffalo calves of age between 8-10 month and average body weight 112 ± 3.30 kg were randomly divided into three treatments (4 calves per treatment). Three isonitrogenous (16.14% CP) and isocaloric (66% TDN) dietary treatments: A) Calcium (Ca) 0.46% + Phosphorus (P) 0.31%; B) Ca 0.59% + P 0.31% and C) Ca 0.75% + P 0.31% on dry matter basis with Ca : P ratios of 1.5:1, 2:1 and 2.5:1, respectively. Levels of Ca were adjusted by addition of varying amount of limestone powder and di-calcium phosphate in total mixed rations (TMR). Animals were fed on 2 kg oats green fodder and TMR on ad-libitum. Feed intake for each animal was recorded daily. Growth was monitored by weighing calves fortnightly. Blood samples were taken pre and 90 days post mineral supplementation approximately 3 hours after morning feeding. At the end of experiment, one week digestibility trial was also conducted. Results revealed that dry matter intake (DMI) was not different among the treatments; whereas, total weight gain, average daily weight gain and FCR were higher (P<0.05) in the treatment C compared with the treatment A. The digestibility of DM was similar among all treatments whereas, the digestibility of CP and CF was higher (P<0.05) in the treatment C compared to the treatment A. Serum P concentration increased (P<0.05) with dietary P; whereas, the serum Ca concentration remained unchanged. It is therefore, concluded that increasing the dietary Ca concentration improved feed intake, weight gain, FCR as well as nutrients digestibility in growing buffalo calves.
Keywords: Buffalo calves; Growth rate; Digestibility; Ca and P ratios; Serum Ca and P levels